Fe-bearing phases in Antarctic carbonaceous chondrites Yamato-82162 and Yamato-86720: A Mossbauer study - Scorzelli,R. B.; Galvao da Silva,E.; Azevedo,I. Souza; Tomeoka,Kazushige (National Institute of Polar Research, 1994)
P(論文) We report the results of variable temperature Mossbauer spectroscopy measurements on samples of Yamato-82162 and Yamato-86720 carbonaceous chondrites. Transmission Mossbauer spectra were taken through the temperature range from 4.2K to 300K. The Mossbauer spectra at room temperature clearly indicate the presence of magnetic splits and quadrupole doublets in both meteorites, which can be attributed to troilite and olivine, respectively. The measurements also indicate the presence of a superparamagnetic component, probably ferryhidrite, in Y-86720 but not in Y-82162. These results are mostly consistent with those obtained by mineralogical studies. However, our Mossbauer measurements indicate the presence of a previously unknown magnetic component having a field of 250kOe in both meteorites; the mineral is unidentified so far. Our study supports the view that these meteorites were affected by thermal metamorphism, and that Y-82162 was less thermally metamorphosed than Y-86720. departmental bulletin paper